2017
DOI: 10.3892/mmr.2017.8317
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin protects endothelial progenitor cells from damage of angiotensin II via activation of ERK1/2‑Nrf2 signaling pathway

Abstract: Endothelial progenitor cell (EPC) dysfunction is associated with the formation of carotid atherosclerosis. It has been demonstrated that angiotensin II (Ang II) may impair the function of EPCs and puerarin, a natural product, possesses cardiovascular protective effects against oxidative stress and inflammation. Therefore, the present study aimed to investigate the beneficial effects of puerarin in Ang II‑induced EPC injury, and to elucidate the underlying mechanisms. Treatment with Ang II suppressed EPC prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In parallel, there is evidence that MACs are also of utmost importance in their contribution to angiogenesis, tissue regeneration and endothelial repair ( 22 , 23 ), where these precursor cells exert paracrine and trophic effects that influence the host microenvironment ( 24 , 25 ). The following sections will describe mechanisms underpinning vascular dysfunction in inflammatory conditions with high risk of cardiovascular disease (CVD) and consider potential therapeutic options aimed at improving progenitor cell reparative function ( 26 , 27 ) as a novel approach to exploit endogenous repair processes.…”
Section: Endothelial Damage and Repair In High-risk Disease Conditionmentioning
confidence: 99%
“…In parallel, there is evidence that MACs are also of utmost importance in their contribution to angiogenesis, tissue regeneration and endothelial repair ( 22 , 23 ), where these precursor cells exert paracrine and trophic effects that influence the host microenvironment ( 24 , 25 ). The following sections will describe mechanisms underpinning vascular dysfunction in inflammatory conditions with high risk of cardiovascular disease (CVD) and consider potential therapeutic options aimed at improving progenitor cell reparative function ( 26 , 27 ) as a novel approach to exploit endogenous repair processes.…”
Section: Endothelial Damage and Repair In High-risk Disease Conditionmentioning
confidence: 99%
“…Puerarin, a major isoflavone isolated from the root of Pueraria lobata, has been reported to treat various cardiovascular diseases, including arterial hypertension, angina, myocardial infarction and arrhythmia (26)(27)(28). Puerarin has anti-atherosclerotic activity in diet-induced atherosclerosis in rabbits and rats (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin has been hypothesized to act in an arginase 2-dependent manner, a mitochondrial enzyme, via modulation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-associated oxidative stress (6,(11)(12)(13). In addition, puerarin alters the production of innate immune cells by regulating the differentiation of progenitor cells via estrogen receptors (14). Previous studies reported the protective effects of puerarin on the viability and function of endothelial progenitor cells derived from bone borrow and peripheral blood (10,14).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, puerarin alters the production of innate immune cells by regulating the differentiation of progenitor cells via estrogen receptors (14). Previous studies reported the protective effects of puerarin on the viability and function of endothelial progenitor cells derived from bone borrow and peripheral blood (10,14). Furthermore, puerarin exhibits ameliorative effects in various inflammatory disorders via inhibiting the degranulation of mast cells, reducing monocyte adhesion to endothelial cells and modifying chemotactic agent expression in cardiac fibrotic tissue (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation